The Meaning of Shaffa in the Qur'an: Semantic Analysis Based on Toshihiko Izutsu's Thought - Rahma Azizi Meliasani; Kharis Nugroho (al-Afkar, Journal For Islamic Studies, 2025)
This paper talks about the semantic meaning of the word Shaffa in the Qur'an. The author uses a semantic approach, which is an analytical study of the key terms of a language with a view that finally arrives at a conceptual meaning or worldview. This study uses a qualitative research motto with a descriptive discussion motto of analysis with the type of literature research. This research was conducted to find the meaning of the word Shaffa. Shaffa is based on the weltanschauung (worldview) of the Qur'an. The author uses Toshihiko Izutsu's semantic approach in finding the meaning of the word saffa because Izutsu offers the concept of letting the Qur'an explain and talk about itself' as it has been known in the science of tafsir called tafsir bi al ma'sur or tafsir of verses with verses'. The meaning of "shaffa" or "line" in the Islamic thought tradition, specifically the one discussed by Toshihiko Izutsu, offers a deeper understanding of the relationship between humans, God, and the universe. In Izutsu's studies, the shaffa is not only seen as a physical structure in religious rituals such as prayers, but also as a symbol of unity and harmony created in the diversity of the people. Izutsu interprets the concept of shaffa as a representation of the metaphysical principles that govern the spiritual world, in which each individual, despite having a separate identity, functions in a greater unity in worship of God. This thought leads to the understanding that shaffa reflects the cosmic order that connects the entire creation, affirming the values of togetherness, discipline, and order in society, ultimately serving as a medium for achieving spiritual closeness to God. Thus, according to Izutsu, the shaffa became an important symbol in explaining the spiritual and social order in Islam that was not only ritualistic, but also philosophical and metaphysical.